Expanding the Phenotypic and Genotypic Spectrum of ARFGEF1-Related Neurodevelopmental Disorder - Xu, Lu; Zhou, Youfeng; Ren, Xiaoyan; Xu, Chenlu; Ren, Rongna; Yan, Xuke; Li, Xuelian; Yang, Huimin; Xu, Xuebin; Guo, Xiaotong; Sheng, Guoxia; Hua, Yi; et al. (Frontiers in Molecular Neuroscience, 2022)
Mono-allelic loss-of-function variants in ARFGEF1 have recently caused a developmental delay, intellectual disability, and epilepsy, with varying clinical expressivity. However, given the clinical heterogeneity and low-penetrance mutations of ARFGEF1-related neurodevelopmental disorder, the robustness of the gene-disease association requires additional evidence. In this study, five novel heterozygous ARFGEF1 variants were identified in five unrelated pediatric patients with neurodevelopmental disorders, including one missense change (c.3539T>G), two canonical splice site variants (c.917-1G>T, c.2850+2T>A), and two frameshift (c.2923_c.2924delCT, c.4951delG) mutations resulting in truncation of ARFGEF1. The pathogenic/likely pathogenic variants presented here will be highly beneficial to patients undergoing genetic testing in the future by providing an expanded reference list of disease-causing variants.